PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU DI SDN MEDAN SATRIA 1 KOTA BEKASI - Hasna Khalishah Fadhilah; Yohamintin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the principal's leadership role in improving teacher professionalism at SDN Medan Satria 1 Bekasi City. The main problem in this study is that there are still teachers who are not optimal in carrying out their professional duties and responsibilities. This research uses a qualitative approach with a case study method. Data collection techniques were carried out through observation, interviews, and documentation, and analyzed using triangulation of sources and techniques. The results showed that principals have important roles as instructional leaders, supervisors, educators, and human resource managers. Communicative, open and supportive leadership has a positive impact on improving the quality of work, initiative and professional ability of teachers. Principals' support for teachers' innovation and self-development also encourages the creation of a productive and reflective work culture. This finding confirms that the success of improving teachers' professionalism is strongly influenced by the adaptive, participatory and visionary leadership style of principals.